Seroprevalence of West Nile virus antibodies in equids in the North-East of Algeria and detection of virus circulation in 2014. (February 2017) - Lafri, Ismail; Prat, Christine M.; Bitam, Idir; Gravier, Patrick; Besbaci, Mohamed; Zeroual, Fayçal; Ben-Mahdi, Meriem Hind; Davoust, Bernard; Leparc-Goffart, Isabelle
Highlights: This study describes the first seroprevalence study of West Nile virus (WNV) antibodies conducted in the equine population in Algeria. Antibodies against WNV were found in 51 samples (seroprevalence 17.4%) of sampled equids, distributed as follows: 19 (seroprevalence 26.8%) horses and 32 (seroprevalence 14.4%) donkeys. We observe a seroconversion in 2 horses, showing WNV circulation in 2014 in this specific region of Algeria. Abstract: West Nile fever (WNF) is a viral disease of wild birds transmitted by mosquitoes. Humans and equids can also be affected and suffer from meningoencephalitis. In Algeria, since the 1994 epidemic, no data on WNV circulation was available until 2012. In September 2012, a fatal human case of WNV neuro-invasive infection occurred in Jijel province. This study describes the first seroprevalence study of West Nile virus (WNV) antibodies conducted in the equine population in Algeria. During 2014, serum samples were collected from 293 equids (222 donkeys and 71 horses) asymptomatic and unvaccinated for WNV in three localities in Northeastern wetlands of Algeria. Antibodies against WNV were found in 51 samples (seroprevalence 17.4%) of sampled equids, distributed as follows: 19 (seroprevalence 26.8%) horses and 32 (seroprevalence 14.4%) donkeys. Moreover 7 horses coming from Blida, in the center of Algeria, were tested before and after an 8-months stay in North-East Algeria. We observe a seroconversion in 2 horses, showing WNV circulation in 2014 in this specific region of Algeria.